ANALISIS PENILAIAN KINERJA KEUANGAN PADA PT. BPR PARO LABA TONDANO, MINAHASA - Natalita Devinia Rondonuwu; Frida Magda Sumual; Olifia Yodiawati Tala (Universitas Methodist Indonesia, 2023)
The purpose of this study was to determine the financial performance of PT BPR Paro Laba Tondano, Minahasa using the profitability ratio approach, solvency ratio, liquidity ratio, and growth ratio for the 2016-2020 period. The secondary data source used was taken directly at PT BPR Paro Laba Tondano, Minahasa. The data collection method used is documentation. This research method is descriptive quantitative. The results showed that the profitability ratio using the ROE ratio showed that the bank was quite capable of earning profits from its own capital. The growth ratio shows the growth per semester continues to decline. Solvency ratios using Debt-to-Equity Ratio show banks are able to pay debts with the capital they have. The growth ratio shows growth from 2016 to 2017 to 2017 to 2018 up, 2017 to 2018 to 2018 to 2019 down, and 2018 to 2019 to 2019 to 2020 back up. Liquidity ratios using Quick Ratio show that banks are less able to fulfill obligations to depositors with the most liquid assets. The growth ratio shows growth from 2016 to 2017 to 2017 to 2018 up, while 2018 to 2019, 2019 to 2020 down.